Development and Evaluation of Valsartan Fast Disintegrating Films - Balakrishna, Dr. T. (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The aim of the present work was to develop and evaluate the fast disintegrating films (FDF) of valsartan which is used for the treatment of hypertension and heart failure. Method: The valsartan fast disintegrating films were prepared by solvent casting method using hydroxylpropyl cellulose, poly vinyl alcohol (PVA), HPMC E5 as film forming agents, Polyethylene glycol 400 as plasticizers and dimethylsulfoxide as penetration enhancer. Results: Valsartan FDF were developed and evaluated for weight uniformity, drug content, film thickness, and folding endurance, the results obtained were within the specified limits. The in vitro diffusion studies were performed using Franz diffusion cell apparatus containing 6.8 pH phosphate buffer as a dissolution media. Conclusion: The FDF prepared with HPMC E5 at 1:3 ratio released the drug up to 98.7% within 5 min which showed the increased solubility, dissolution rate flexibility, and tensile strength of the films when compared to formulation prepared with hydroxypropyl cellulose and PVA. The Fourier-transform infrared studies were conducted for pure drug, polymers and optimized formulation V9 which indicated that were no incompatibilities found between the drug and polymers used in the present studies. Scanning electron microscopy analysis was performed for pure drug, polymers, and optimized formulation V9 which showed that they were no surface fractures and cracks in the films.